Real-World Evidence of the Neutralizing Monoclonal Antibody Sotrovimab for Preventing Hospitalization and Mortality in COVID-19 Outpatients. (16th May 2022) - Aggarwal, Neil R; Beaty, Laurel E; Bennett, Tellen D; Carlson, Nichole E; Davis, Christopher B; Kwan, Bethany M; Mayer, David A; Ong, Toan C; Russell, Seth; Steele, Jeffrey; Wogu, Adane F; Wynia, Matthew K; et al.
Abstract: Background: It is not known whether sotrovimab, a neutralizing monoclonal antibody (mAb) treatment authorized for early symptomatic coronavirus disease 2019 (COVID-19) patients, is also effective in preventing the progression of severe disease and mortality following severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) Delta variant infection. Methods: In an observational cohort study of nonhospitalized adult patients with SARS-CoV-2 infection, 1 October 2021–11 December 2021, using electronic health records from a statewide health system plus state-level vaccine and mortality data, we used propensity matching to select 3 patients not receiving mAbs for each patient who received outpatient sotrovimab treatment. The primary outcome was 28-day hospitalization; secondary outcomes included mortality and severity of hospitalization. Results: Of 10 036 patients with SARS-CoV-2 infection, 522 receiving sotrovimab were matched to 1563 not receiving mAbs. Compared to mAb-untreated patients, sotrovimab treatment was associated with a 63% decrease in the odds of all-cause hospitalization (raw rate 2.1% vs 5.7%; adjusted odds ratio [aOR], 0.37; 95% confidence interval [CI], .19–.66) and an 89% decrease in the odds of all-cause 28-day mortality (raw rate 0% vs 1.0%; aOR, 0.11; 95% CI, .0–.79), and may reduce respiratory disease severity among those hospitalized. Conclusions: Real-world evidence demonstrated sotrovimab effectiveness in reducing hospitalization and all-cause 28-day mortality among COVID-19 outpatients during the Delta variant phase. Abstract : Real-world evidence demonstrates that sotrovimab, a neutralizing monoclonal antibody (mAb), significantly reduces 28-day hospitalization and mortality rates when administered to high-risk outpatients recently infected with SARS-CoV-2 during the Delta variant phase, compared to a propensity-matched cohort of mAb-untreated outpatients.